ANALISIS HUBUNGAN ASPEK SOSIO DEMOGRAFI TERHADAP STATUS GIZI BALITA - Khodija, Unziya; Nursyam, Dian Eka; Blongkod, Fitriani Rahmatismi; Ardhiani, Innas Tiara (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Cases of malnutrition in the Oka Health Center working area show an increasing trend from year to year. Of the entire working area, the most cases of malnutrition are found in Lamawalang Village. The purpose of the study was to determine the relationship of socio-demographic aspects to the nutritional status of toddlers. The research design used in this study was cross sectional. The research was conducted in Lamawalang Village. The research was conducted in February 2024. The population is all mothers who have toddlers aged 12-59 months in Lamawalang Village totaling 54 toddlers as well as the research sample. The sampling technique used in this study was total sampling. Data analysis was done univariate and bivariate. The results showed that there was a relationship between maternal education (p value: 0.043) and family income (p value: 0.038) on nutritional status in toddlers. It is recommended that the Puskesmas can add educational programs to mothers of toddlers about the importance of nutrition in toddlers.Keywords: Toddlers, Income, Maternal Education